2021
DOI: 10.2147/phmt.s294739
|View full text |Cite
|
Sign up to set email alerts
|

Immunization Status and Challenges During COVID-19 and Associated Factors Among Children Aged 10–23 Months in South Region, Ethiopia 2020

Abstract: Background The worldwide COVID-19 pandemic is overstressing health systems and Essential health services and vaccination services are disrupted. Immunization is a confirmed gizmo for governing and even eliminating communicable diseases. Objective This study aims to assess the challenge and status of immunization during COVID-19 and associated factors among children aged 10–23 months south Nation Nationality and People Region Ethiopia. Methods and Materials: community-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
34
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(35 citation statements)
references
References 18 publications
0
34
0
1
Order By: Relevance
“…The pandemic is likely to have added to this number among children of mothers with low levels of education and in low-income households. Similar reductions in Ethiopia, reported in the two studies [25,26] included in the review, are likely to affect countrywide vaccination coverage and GAVP targets. Nonetheless, it is difficult to gauge the probable extent of the reduction as the numbers in the lowest education group (cannot read or write) in both studies are very low.…”
Section: Discussionmentioning
confidence: 55%
See 4 more Smart Citations
“…The pandemic is likely to have added to this number among children of mothers with low levels of education and in low-income households. Similar reductions in Ethiopia, reported in the two studies [25,26] included in the review, are likely to affect countrywide vaccination coverage and GAVP targets. Nonetheless, it is difficult to gauge the probable extent of the reduction as the numbers in the lowest education group (cannot read or write) in both studies are very low.…”
Section: Discussionmentioning
confidence: 55%
“…The included studies used several approaches to study inequities in childhood vaccination inequities. Country-level income categories as defined by the World Bank ( accessed on 3 May 2022) to study variations in routine vaccination rates were reported for child populations in two studies for low-income countries (studies from Ethiopia [ 25 , 26 ]), three for lower-middle-income countries (studies from India [ 20 ] and Pakistan [ 14 , 16 ]), three for upper-middle-income countries (studies from Brazil [ 27 ], China [ 28 ] and Colombia [ 21 ]), four for high-income countries (three US studies [ 22 , 23 , 24 ] and UK [ 15 ]) and in a study comparing nine middle-income countries with 16 high-income countries [ 29 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations